Impact of “Immediate Kangaroo Mother Care” on Survival of Low Birth Weight Neonates in a Tertiary Care Centre: A Prospective Cohort Study - Talikoti, Mallikarjun; Kundargi, Deepa; Charki, Siddu; Rodgi, Chinmaya; Patil, M.M. (International Journal of Child Health and Nutrition, 2024)
Background: “Kangaroo mother care,” a type of newborn care involving skin-to-skin contact with the mother or other caregiver (grandmother), reduces mortality in neonates with low birth weight (< 2 kg) when initiated after stabilization, but the majority of deaths occur before stabilization. The safety and efficacy of kangaroo mother care initiated soon after birth among neonates with low birth weight iKMC is uncertain. Methods: We conducted a prospective cohort study involving neonates with a birth weight < 1.8 kg who were assigned to receive immediate kangaroo mother care (intervention) or conventional care in a radiant warmer until their condition stabilized and kangaroo mother care after that (control). The primary outcomes were death in the neonatal period (the first 28 days of life) and the first 72 hours of life. Results: Two hundred eleven neonates and their mothers were assigned to the intervention group (106 neonates with their mothers) or the control group (105 neonates with their mothers). The median daily duration of skin-to-skin contact in the neonatal intensive care unit was 9.9 hours (interquartile range, 6.0 to 15.7) in the intervention group and 3.5 hours (interquartile range, 1.3 to 6.3) in the control group. Neonatal death occurred in the first 28 days in 12% neonates in the intervention group and 15.7% neonates in the control group (relative risk of death, 0.75; 95% confidence interval [CI], 0.64 to 0.89; P=0.001); neonatal death in the first 72 hours of life occurred in 4.6% neonates in the intervention group and 5.8% neonates in the control group (Relative risk of death, 0.77; 95% CI, 0.58to 1.04; P = 0.09). Conclusions: Among neonates with a birth weight < 1.8 kg, those who received immediate kangaroo mother care had lower mortality at 28 days than those who received conventional care with kangaroo mother care initiated after stabilization; the between-group difference favoring immediate kangaroo mother care at 72 hours was not significant.